Violência e gênero na Atenção Primária em Saúde - CHERLEN AIDANO MONTEIRO CLEMENTE (2015)
This study examines the perceptions of professionals and users in the Primary Health Care (PHC) on gender relations, specifically, what both think about the role of women in society, comparing such perceptions between these two groups investigated in Ribeirão das Neves - MG. The survey was conducted in all 58 Municipality Health Units and the final sample of users, calculated with margin of error of 3.71% based on the estimated population, totaling 628 users. About the Health Care professionals, all that were present attended of the survey, a total of 300. The data were stored in databases using the Statistical Package for the Social Sciences - SPSS. Descriptive analysis was performed on the data, simple and cross frequency distribution, graphical analysis via bar graphs and indicators thematic maps of general agreement, conceptions of gender, physical violence and sexual violence, of users versus professionals. To analyze the data, positive answers indexes were created, that is, appropriate and devoid of prejudice and domination responses to the asked questions. Therefore, values 1 for responses were involving concepts related to gender relations guided by equality and respect, and values -1 for guided responses in inequality and domination. Thus, four indices were constructed, form the Gender Relations group variables, being the first representing the consolidated total score of all the group's answers "Gender Relations" (IRP-General); the second presenting the consolidated score only of Gender Concepts subgroup responses (IRP - General), the third representing the consolidated score only for the variables relating to Gender Concepts group of physical violence (IRP Physical Violence). The fourth, representing the consolidated score only of the variable subgroup Sexual violence (IRP sexual Violence). Standardization of the IRP was done to avoid too high or too low values and ensure that the index stayed within the range 0 to 1. The closer to 1, more positive responses, meaning, therefore, the adoption of values concerning relations was carried out gender more humane and protective.  At the end of the survey it was revealed that the general median IRP was around 0.70 for users and 0.48 for professionals, the IRP - Concepts for users was 0.50 and 0.38 for the professionals, for answers on the IRP-Violence Sexual and IRP-Physical Violence, the average median index was around 1.00 for the two categories of respondents. Results warn that the conceptions of gender relations for both professionals and the users are only protective from the moment in which violence already is established as physical or sexual. And the most worrying is that the rates of positive responses from the professionals are worse than that from the users. This indicates that in Ribeirao das Neves, as around the world, there are still great prejudices against women. And more and more professionals need to be trained and sensitized on this issue, to really act preventively, more humane and protective because postures in favor of the defense of women begin to be significant only when violence become physical or sexual.